Analysis of the evolution of labor market flows in Argentina - Semeshenko, Viktoriya (2021)
Labor mobility plays an important role for macroeconomic analysis. Employment flows carry information about the productive structure, diffusing knowledge among economic activities. Using administrative records for Argentina for 1996-2018 at four different levels of granularity, we explore the networks of inter-industry connections and characterise underlying structural and dynamic aspects of the national productive structure. Our analysis suggests that in order to appreciate the temporal evolution of labor flows, more disaggregated data can bring up a richer picture than looking at the evolution of aggregated labor flows.